Genetic inactivation of the allograft inflammatory factor‐1 locus. Issue 10 (30th August 2013) - Casimiro, Isabel; Chinnasamy, Prameladevi; Sibinga, Nicholas E. S.
<x xml:space="preserve">Abstract</x> Allograft inflammatory factor‐1 (Aif‐1) is a 17 kDa EF hand motif‐bearing protein expressed primarily in developing spermatids and cells of monocyte/macrophage lineage. Increased Aif‐1 expression has been identified in clinically important conditions, including rheumatoid arthritis, systemic sclerosis, endometriosis, and transplant‐associated arteriosclerosis. Largely similar gene products arising from the same locus are known as ionized Ca2+ binding adapter‐1 (Iba1), microglial response factor‐1 (MRF1), and daintain; Iba1 in particular has emerged as a histologic marker of microglia and their activation in pathologic CNS conditions, including the response to facial nerve axotomy and stroke, uveitis, and experimental autoimmune neuritis and encephalomyelitis. Nevertheless, how aif‐1 gene products affect cellular function is only partly understood, and the physiologic significance of these products for male fertility, immune system development, and inflammation has not been described. To permit such investigations, we generated a mouse line with targeted deletion of the coding regions of the aif‐1 gene. Here we report that mice lacking Aif‐1 breed well and show normal post‐natal growth, but show resistance to disease in a model of collagen‐induced arthritis. We anticipate that these mice will be useful for studies of Aif‐1 function in a variety of immune and inflammatory disease models. genesis 51:734–740. © 2013 Wiley Periodicals, Inc.